Intercropping Urochloa brizantha and sorghum inoculated with Azospirillum brasilense for silage (Revista Ciência Agronômica, 2018)
Livestock performance in the Brazilian Cerrado has been limited by the low availability of good qualityfodder, especially during periods of low rainfall. The aim of this study was to evaluate growth and dry matter productionin two cultivars of sorghum, inoculated or not with diazotrophic bacteria, and as a monocrop or intercropped with palisadegrass under a system of crop-livestock integration. The experiments were carried out in the field in the Cerrado regionduring the autumn-winter period of 2015 and 2016, on the experimental farm of the Faculty of Engineering at Ilha Solteira,UNESP, in Selvíria, in the State of Mato Groso do Sul, Brazil (MS). A randomised complete block experimental design wasused in a 2 x 2 x 2 factorial scheme with four replications. The treatments corresponded to two agricultural years (2015 and2016); the cultivation of dual-purpose grain sorghum, alone or intercropped with palisade grass; with or without inoculationof the sorghum seeds with the bacterium Azospirillum brasilense. The dry matter production of the plant components andplant growth were evaluated for the preparation of silage. Inoculation of sorghum seeds with the bacterium Azospirillumbrasilense increases the production of plant dry matter for silage, irrespective of the cultivar or intercrop. Dual-purposegrain sorghum intercropped with palisade grass is a viable agronomic system for producing plant matter for silage duringthe autumn season.